Effectiveness of the Utilization of SIMDIKLAT Application in Education and Training Activities - Sirajuddin Saleh; Dilla Septianti; Muh. Darwis (ASHA Publishing, 2024)
This study aims to analyze the effectiveness of the implementation of the Education and Training Management Information System (SIMDIKLAT) in the implementation of education and training programs at the Makassar Religious Education and Training Center. Using a qualitative approach with purposive sampling techniques, data were collected through participatory observation, in-depth interviews, and documentation studies. Data analysis was carried out using the Miles and Huberman method, including data reduction, data presentation, and conclusion drawn. The results of the study show that the implementation of SIMDIKLAT has contributed positively to the effectiveness of the management of training activities, especially in terms of accuracy, relevance, and timeliness of the information produced. However, this study also identified several significant challenges, including: (1) the limitation of competent human resources in the operation of SIMDIKLAT, and (2) the lack of comprehensive training for training participants and staff in the use of the system. SIMDIKLAT has increased the efficiency of training management, the optimization of its potential is still constrained by organizational and technical factors. The theoretical and practical implications of these findings are discussed, including recommendations for the development of policies and strategies for the implementation of management information systems in the context of government education and training institutions.